2011
DOI: 10.1111/j.1468-0432.2011.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Work–family Life in Academia: The Power of Time

Abstract: In the article we analyse the structuring of time among academic employees in Iceland, how they organize and reconcile their work and family life and whether gender is a defining factor in this context. Our analysis shows clear gender differences in time use. Although flexible working hours help academic parents to organize their working day and fulfil the ever‐changing needs of family members, the women, rather than men interviewed, seem to be stuck with the responsibility of domestic and caring issues becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 20 publications
2
135
2
3
Order By: Relevance
“…Domestic work, in most cases combined with other activities, has been reported in the literature as a stress factor. (12,13) However, in the present study, it was identified as a protective factor for gastric disorders. This finding underscores the effort to correlate food culture with its behavioral effects.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Domestic work, in most cases combined with other activities, has been reported in the literature as a stress factor. (12,13) However, in the present study, it was identified as a protective factor for gastric disorders. This finding underscores the effort to correlate food culture with its behavioral effects.…”
Section: Discussioncontrasting
confidence: 58%
“…A previous study involving men and women and investigating on the use of their time to reconcile work and family life indicated that women were tied to domestic responsibilities and that this might contribute to increased stress. (12) A study on the inequality of domestic work in British couples showed that the women felt burdened not only by the domestic work but also other activities and by not sharing household chores with their companions. (13) Therefore, assistance to female rural workers with gastric disorders needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It can therefore be expected that, since working long hours has become the norm in academia, the WLC experienced by academics may not be very high. However, various studies have found that academics who engage in supplemental work practices at home still do experience higher levels of WLC (Currie & Eveline, 2010;O'Laughlin & Bischoff, 2005;Heijstra & Rafnsdóttir, 2010;Rafnsdóttir & Heijstra, 2011). In addition, Fenner and Renn (2004) Research also suggests that demographic factors such as gender, parental status, marital status and job position play an important role in influencing this relationship (Boswell & Olson-Buchanan, 2007;Parasuraman & Simmers, 2001;Venkatesh & Vitalari, 1992).…”
Section: Gender Tasw and Wlcmentioning
confidence: 99%
“…It can therefore be expected that, since working long hours has become the norm in academia, the WLC experienced by academics may not be very high. However, various studies have found that academics who engage in supplemental work practices at home still do experience higher levels of WLC (Currie & Eveline, 2010;O'Laughlin & Bischoff, 2005;Heijstra & Rafnsdóttir, 2010;Rafnsdóttir & Heijstra, 2011). In addition, Fenner and Renn (2004) suggest that time and boundary management skills mediate the relationship between TASW and WLC.…”
Section: Marital Status Children Tasw and Wlcmentioning
confidence: 99%
“…ICTs have indeed empowered academics with more autonomy and flexibility (Araújo, 2008). Furthermore, ICTs have also consequently created additional opportunities for academics to work from home, enabling them to balance their work and family demands (Araújo, 2008;Currie & Eveline, 2010;Rafnsdóttir & Heijstra, 2011).…”
Section: Work-life Conflictmentioning
confidence: 99%